Dependence of near‐surface similarity scaling on the anisotropy of atmospheric turbulence. (28th August 2018) - Stiperski, Ivana; Calaf, Marc
Abstract : Turbulence data from the CASES‐99 field experiment, over comparatively horizontally homogeneous and flat terrain, are separated based on the anisotropy of the Reynolds stress tensor (into isotropic, two‐component axisymmetric and one‐component turbulence) and flux‐variance similarity scaling relations are tested. Results illustrate that different states of anisotropy correspond to different similarity relations, especially under unstable stratification. Experimental data with close to isotropic turbulence match similarity relationships well. On the other hand, very anisotropic turbulence deviates significantly from the traditional scaling relations. We examine in detail the characteristics of these states of anisotropy, identify conditions in which they occur and connect them with different governing parameters. The governing parameters of turbulence anisotropy are shown to be different for stable and unstable stratification, but are able to delineate clearly the conditions in which each of the anisotropy states occurs. Abstract : Near‐surface similarity relations are examined in the light of turbulence anisotropy. Isotropic turbulence is found to fit traditional scaling well, while highly anisotropic data deviate significantly from the scaling. Anisotropy also explains the large scatter in scaled horizontal velocity variances. Parameters governing anisotropy in unstable stratification are found to be wind shear and stability and, for stable stratification, wind speed and turbulent kinetic energy.